Correlation of Bromodomain Protein BRD4 Expression With Epithelial–Mesenchymal Transition and Disease Severity in Chronic Rhinosinusitis With Nasal Polyps - Zhou, Xuanchen; Cui, Zhaoyang; Liu, Yiqing; Yue, Zhiyong; Xie, Fengyang; Ding, Ling; Xu, Shuai; Han, Jie; Zhang, Hong (Frontiers in Medicine, 2020)
Objectives: This study aimed to explore the relationship between BRD4 and EMT and disease severity in CRSwNP. Material and Methods: we performed immunofluorescent (IF) staining to evaluate the expression of BRD4 in polyps tissue of CRSwNP and inferior turbinate mucosa of healthy controls. The relationship between BRD4 and EMT was evaluated by the BRD inhibitor JQ1 and BRD4 siRNA in primary human nasal polyp-derived epithelial cells (hPDECs). Disease severity was scored by using the Lund-Mackay scores of paranasal sinus CT scans Results: The expression of BRD4 in patients with CRSwNP was significantly higher than healthy controls. The loss of BRD4 function by the BRD inhibitor JQ1 and BRD4 siRNA resulted in reduction of E-cadherin, increasing of Vimentin and Snai1 mRNA expression. And, the expression of BRD4 was related to the total CT scan scores (r=0.4682, p=0.0210). Conclusions: BRD4 was higher expression in CRSwNP than healthy controls and might associate to EMT of CRSwNP. BRD4 mRNA expression was associated with disease severity in CRSwNP.